The Relationship Between Content Marketing, Live Streaming, Endorsement, and Purchasing Decisions on the Tiktokshop Platform and Its Views on Islam - Niken Lestari; Mukhsinun Mukhsinun; Naeli Indah Munib (Universitas KH. Abdul Chalim Mojokerto, 2025)
TikTok Shop is a favorite e-commerce platform. The final purchase decision is very important for consumers to determine the appropriateness of the product. Content marketing, live streaming, and endorsements are important variables that influence product purchase decisions at TikTok Shop. Therefore, this study aims to analyze the direct impact of content marketing, live streaming, and endorsements on purchasing considerations. This study uses a quantitative research approach with a causal association method. Primary data was collected by distributing questionnaires online to Tiktok application users who have experience using Tiktok Shop at least 17 years old in the Kebumen area, Central Java. Samples were randomly selected with a specified time limit from the target population. The data were processed using structural equation modeling (SEM) with multiple mediator analysis used for modeling. The research findings from a sample of 105 respondents show that the R Square value of endorsement is 0.623, indicating that 62.3% of the variation in endorsement can be explained by content marketing and live streaming. Similarly, the R Square value of purchase decision 0.631 indicates that 63.1% of the variation in purchase decision can be explained by content marketing, live streaming, and endorsement. Meanwhile, the R Square value of live streaming of 0.451 indicates that 45.1% of the variation in live streaming can be explained by content marketing. the majority of respondents, namely 60%, strongly agree, while 39% agree, that when shopping at TikTok Shop, it is important to do research first regarding product information. This is in line with the precautionary principle commanded in the Quran letter Al-Hujurat verse 6, which advises Muslims to verify information before trusting it. In addition, 32% of respondents agreed and 67% of respondents strongly agreed with the importance of not rushing or overspending when buying products.